Caracterização dos moradores expostos a agrotóxicos de um assentamento próximo à cidade de Cascavel-PR - Miranda, Lidiane Alves de (2021)
The consumption of pesticides has been increasingly used in agricultural production in our country, and its excessive use has made it a public and environmental health problem, representing a risk to the environment and human health, especially to rural workers and their families, in addition to society as a whole, as they live in this environment and consume food from agriculture. The present study, with a qualiquantitative focus, will consist of 2 steps, the first will be a descriptive survey of selfreported health problems by 8 families exposed to pesticides, the second will be verified the presence of pesticides and physicochemical characteristics of the surrounding soil of the residences of families residing in a settlement in the rural area in the city of Cascavel-PR. The purpose of the study is to characterize this population through the survey of morbidities and correlate the physical-chemical characteristics of the soil, there is a possible chronic poisoning. Around this settlement there are private properties with frequent spraying of pesticides in agriculture, thus causing environmental contamination, and the residents of this place have presented health problems, possibly related to this exposure.